If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 4 = 5(y + -4) Reorder the terms: 4 + 9y = 5(y + -4) Reorder the terms: 4 + 9y = 5(-4 + y) 4 + 9y = (-4 * 5 + y * 5) 4 + 9y = (-20 + 5y) Solving 4 + 9y = -20 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 4 + 9y + -5y = -20 + 5y + -5y Combine like terms: 9y + -5y = 4y 4 + 4y = -20 + 5y + -5y Combine like terms: 5y + -5y = 0 4 + 4y = -20 + 0 4 + 4y = -20 Add '-4' to each side of the equation. 4 + -4 + 4y = -20 + -4 Combine like terms: 4 + -4 = 0 0 + 4y = -20 + -4 4y = -20 + -4 Combine like terms: -20 + -4 = -24 4y = -24 Divide each side by '4'. y = -6 Simplifying y = -6
| 5x+50=5x+50 | | 8(6x-5)=4760 | | y-4=1/2(x-15) | | -2.5+1.5y=11-3y | | Cos5x=1/2 | | u^2-11u-18=0 | | x(a+b)= | | -9-19=-14-14 | | 6(3/4)-1 | | -1(2)=2-4 | | 9(2x+5)=595 | | 8x+27-12y=7 | | 2x+48=2x-24 | | 0.75n-6=n+3 | | 34-5x+2(x-3)=2 | | (1/4-1/2);(3/4,2) | | x^3+y^3=91 | | xa^2+xb=c | | 5x+8=-167 | | 11-2x-6y=-11 | | 2x-3/5=3x+2 | | 6a+4b-a+9b= | | 7(4x+9)=165 | | -1=28x+21 | | 7a-4=10-2a-41 | | -4v^2+28v+32=0 | | 12-x/8=-1 | | 3a-a+5-6= | | 4+49x=21x+16 | | 5(6x-4)=190 | | 4.2x=-24x-48 | | (9-u)(2u-1)=0 |